2023
DOI: 10.1002/bse.3579
|View full text |Cite
|
Sign up to set email alerts
|

Can blockchain technologies enhance environmental sustainable development goals performance in manufacturing firms? Potential mediation of green supply chain management practices

Amin Jan,
Anas A. Salameh,
Haseeb Ur Rahman
et al.

Abstract: The nexus between manufacturing firms and the green environment is unavoidable. It is merely due to the huge waste generation and greenhouse gas emissions resulting from large‐scale production and complex supply chain management processes involved in manufacturing firms. Continuation of the traditional business practices during Industry 4.0 made it impossible for the manufacturing firm to commit to green environmental practices and comply with environmental SDGs. At odd, it requires novel business strategies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Karim et al [155] and Khan et al [156], respectively, have demonstrated the crucial role of green supply chain management (GSCM) in advancing the environmental performance of organizations and mediating the impact of Industry 4.0 technologies on operational and innovation performances. Jan et al [157] underscore the strategic significance of green supply chain management (GSCM) in fostering sustainability and resilience within manufacturing supply chains. These studies collectively confirm the crucial role of green logistics in mediating the relationship between green innovation strategies and improved supply chain resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Karim et al [155] and Khan et al [156], respectively, have demonstrated the crucial role of green supply chain management (GSCM) in advancing the environmental performance of organizations and mediating the impact of Industry 4.0 technologies on operational and innovation performances. Jan et al [157] underscore the strategic significance of green supply chain management (GSCM) in fostering sustainability and resilience within manufacturing supply chains. These studies collectively confirm the crucial role of green logistics in mediating the relationship between green innovation strategies and improved supply chain resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Many scholars have analyzed the risks of traditional agricultural product supply chains and green supply chains in detail (Ngo et al, 2024;Sharma et al, 2020;Sridhar et al, 2022). The research on the green supply chain of agricultural products mainly focuses on improving the efficiency of the supply chain through technological innovation (Cao et al, 2022;Demestichas et al, 2020;Ersoy et al, 2022;Jan et al, 2023;Saurabh & Dey, 2021;Yadav et al, 2020), supply chain construction, risk categories (Li, 2012), and balancing the interests of all parties (Yu & Khan, 2021). However, the research and discussion on the risks of green supply chains of agricultural products are still insufficient.…”
mentioning
confidence: 99%